N‐linked glycan truncation causes enhanced clearance of plasma‐derived von Willebrand factor. (9th December 2016) - O'Sullivan, J. M.; Aguila, S.; McRae, E.; Ward, S. E.; Rawley, O.; Fallon, P. G.; Brophy, T. M.; Preston, R. J. S.; Brady, L.; Sheils, O.; Chion, A.; O'Donnell, J. S.
Abstract : Essentials von Willebrands factor (VWF) glycosylation plays a key role in modulating in vivo clearance. VWF glycoforms were used to examine the role of specific glycan moieties in regulating clearance. Reduction in sialylation resulted in enhanced VWF clearance through asialoglycoprotein receptor. Progressive VWF N‐linked glycan trimming resulted in increased macrophage‐mediated clearance. Click to hear Dr Denis discuss clearance of von Willebrand factor in a free presentation from the ISTH Academy Summary: Background: Enhanced von Willebrand factor (VWF) clearance is important in the etiology of both type 1 and type 2 von Willebrand disease (VWD). In addition, previous studies have demonstrated that VWF glycans play a key role in regulating in vivo clearance. However, the molecular mechanisms underlying VWF clearance remain poorly understood. Objective: To define the molecular mechanisms through which VWF N‐linked glycan structures influence in vivo clearance. Methods: By use of a series of exoglycosidases, different plasma‐derived VWF (pd‐VWF) glycoforms were generated. In vivo clearance of these glycoforms was then assessed in VWF −/− mice in the presence or absence of inhibitors of asialoglycoprotein receptor (ASGPR), or following clodronate‐induced macrophage depletion. Results: Reduced amounts of N‐linked and O‐linked sialylation resulted in enhanced pd‐VWF clearance modulated via ASGPR. In addition to this role of terminal sialylation, we further observed that progressive N‐linked glycan trimming also resulted in markedly enhanced VWF clearance. Furthermore, these additional N‐linked glycan effects on clearance were ASGPR‐independent, and instead involved enhanced macrophage clearance that was mediated, at least in part, through LDL receptor‐related protein 1. Conclusion: The carbohydrate determinants expressed on VWF regulate susceptibility to proteolysis by ADAMTS‐13. In addition, our findings now further demonstrate that non‐sialic acid carbohydrate determinants expressed on VWF also play an unexpectedly important role in modulating in vivo clearance through both hepatic ASGPR‐dependent and macrophage‐dependent pathways. In addition, these data further support the hypothesis that variation in VWF glycosylation may be important in the pathophysiology underlying type 1C VWD.